2010
DOI: 10.1007/s11748-009-0529-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of opium use on short-term outcome in patients undergoing coronary artery bypass surgery

Abstract: Continued use of opium is a significant predictor of rehospitalization with a cardiac cause within 6 months of CABG surgery. This may be partly due to the low compliance of these patients with treatment recommendations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 22 publications
1
30
0
Order By: Relevance
“…In a historical cohort study of 110 patients addicted to opium over 1.5 years, Nemati et al 33 reported a significant increase in hemorrhage and blood transfusions after CABG, consistent with our findings. A prospective review of 56 opium-using patients conducted by Safaii and Kazemi 17 reported no difference in mortality and comparable complication rates (pulmonary complications, 14.2%; blood transfusions, 33.3%), but complications did not significantly differ between opium users and nonusers. It is important to note that the population studied differs from ours in that opium use in the Middle East may not directly translate to the opioid-type drugs used in the United States.…”
Section: Discussionmentioning
confidence: 97%
“…In a historical cohort study of 110 patients addicted to opium over 1.5 years, Nemati et al 33 reported a significant increase in hemorrhage and blood transfusions after CABG, consistent with our findings. A prospective review of 56 opium-using patients conducted by Safaii and Kazemi 17 reported no difference in mortality and comparable complication rates (pulmonary complications, 14.2%; blood transfusions, 33.3%), but complications did not significantly differ between opium users and nonusers. It is important to note that the population studied differs from ours in that opium use in the Middle East may not directly translate to the opioid-type drugs used in the United States.…”
Section: Discussionmentioning
confidence: 97%
“…But findings of Sadeghian et al[14]’s research on 4398 isolated CABG patients and opium dependence rate of 15.6%, found no relationship between post CABG in hospital complications and opium addiction. But on the other hand, in a study conducted by Safaii et al[15] on 6-mo outcomes of CABG patients, opium usage leaded to more readmission following CABG operation.…”
Section: Discussionmentioning
confidence: 97%
“…In a propensity-matched study, Sadeghian et al[14] found no association between opium dependence and post CABG in-hospital complications. On the other hand, in Safaii et al[15]’s study, six months post-CABG readmission was significantly more frequent in opium users. However, there are few evidences to clarify the definite relationship between chronic opium abuse and long-term survival in cardiac surgery patients.…”
Section: Introductionmentioning
confidence: 87%
“…11 A somewhat similar effect has been reported after total hip and knee arthroplasty and CABG but this needs more investigation. 12,13 Studies have shown a significant link between unemployment and risk of blood transfusion in spine surgery patients, increased LOS and decreased health-related quality of life after surgery. 4,14,15 We add that unemployment status in spinal surgery patients is associated with higher comorbidity rates which consume additional healthcare resources.…”
Section: Discussionmentioning
confidence: 99%